Deletion of the clock gene Period2 (Per2) in glial cells alters mood-related behavior in mice - Tomaz Martini (Nature Portfolio, 2021)
Abstract The circadian clock regulates many biochemical and physiological pathways, and lack of clock genes, such as Period (Per) 2, affects not only circadian activity rhythms, but can also modulate feeding and mood-related behaviors. However, it is not known how cell-type specific expression of Per2 contributes to these behaviors. In this study, we find that Per2 in glial cells is important for balancing mood-related behaviors, without affecting circadian activity parameters. Genetic and adeno-associated virus-mediated deletion of Per2 in glial cells of mice leads to reduced despair and anxiety. This is paralleled by an increase of the GABA transporter 2 (Gat2/Slc6a13) and Dopamine receptor D3 (Drd3) mRNA, and a reduction of glutamate levels in the nucleus accumbens (NAc). Interestingly, neuronal Per2 knock-out also reduces despair, but does not influence anxiety. The change in mood-related behavior is not a result of a defective molecular clock, as glial Bmal1 deletion has no effect on neither despair nor anxiety. Exclusive deletion of Per2 in glia of the NAc reduced despair, but had no influence on anxiety. Our data provide strong evidence for an important role of glial Per2 in regulating mood-related behavior.